THE IMPLEMENTATION OF POEW IN TEACHING WRITING - Sianna, Sianna; Syawal, Syawal (International Journal of Language Education, 2017)
This research was aimed to investigate how significant the implementation of POEW model improved the students’ writing ability. It was conducted using a quasi-experimental method with two pretest-posttest group design. It was implemented to the third semester students of English department of Universitas Muhammadiyah Parepare in academic year 2016/2017. At first, the researcher implemented POEW model to treat the students in teaching writing. After that, they were tested to find out their ability after being treated through POEW model. Data were analyzed quantitatively using 21.0 version of SPSS program.The result indicated that the students who were treated through POEW model have significant improvement in their writing ability than the students who were not. It is found that the significant value (0.000) was lower than the probability value (0.05). This means that there was a significant difference between the students’ writing ability before and after being taught through POEW model where the students’ writing ability improved significantly in posttest (after being taught through POEW model). The mean score of posttest of the students in experimental class (72.40) was higher than the students in control class (62.46) which indicated that the students ability in the experimental class was better than the students in control class. The students ability in experimental class was improved from 61.24 to 72.40 while in control class only from 61.36 to 62.46. Besides that, the standar deviation in experimental class (7.832) was also lower than in control class (8.364) which indicated that the students ability in experimental class was slightly similar to control class